2001
DOI: 10.1097/00001888-200112000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Efficacy of Staff Versus Housestaff Instruction in an Intervention to Improve Hypertension Management

Abstract: This intervention was effective in improving providers' compliance with a hypertension practice guideline, but only when led by a faculty opinion leader. A resident instructor using the same format was unable to change the providers' behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 5 publications
3
11
0
Order By: Relevance
“…It is likely that this finding indicates a general distrust of change and practices that are perceived as different from usual care where leadership is suboptimal. These findings suggest that having a positively perceived local opinion leader to introduce and guide change in practice may facilitate receptivity to change in providers' behavior (59). Consistent with the above findings, transactional leadership was positively associated with scores on both the openness subscale and the total EBPAS scale.…”
Section: Discussionsupporting
confidence: 78%
“…It is likely that this finding indicates a general distrust of change and practices that are perceived as different from usual care where leadership is suboptimal. These findings suggest that having a positively perceived local opinion leader to introduce and guide change in practice may facilitate receptivity to change in providers' behavior (59). Consistent with the above findings, transactional leadership was positively associated with scores on both the openness subscale and the total EBPAS scale.…”
Section: Discussionsupporting
confidence: 78%
“…The perceived time barrier in early resident development (years 1–2), may be related to a focus on hospital based medicine, with less time spent in the out patient clinic. The more experienced third year residents reported that a lack of specific guideline instruction and staff role modeling were the most important CPG compliance barriers [2,17]. Positive pre-intervention attitudes toward the guidelines were demonstrated in this study [Figure 2] and in previous studies [2,11].…”
Section: Discussionsupporting
confidence: 65%
“…6,[14][15][16][17][18] One randomized controlled trial using chart audit of 10-12 patients per resident, report cards assessing 78 audit items, and a 10-to 15-minute feedback session did not demonstrate improved patient management. 19 Possible reasons for the lack of benefit with this approach include the limited number of patients assessed per resident; diffuse nature of the feedback; and the single, brief feedback session.…”
Section: Discussionmentioning
confidence: 95%